Taphonomy of microorganisms and microbial microtextures at sulfidic hydrothermal vents: A case study from the Roman Ruins black smokers, Eastern Manus Basin. Issue 4 (22nd March 2022) - Baumgartner, Raphael J.; Hu, Siyu; Van Kranendonk, Martin J.; Verrall, Michael
Abstract: Biological activity at deep‐sea hydrothermal chimneys is driven by chemotrophic microorganisms that metabolize chemicals from the venting high‐temperature fluids. Understanding taphonomy and microbial microtextures in such environments is a necessity for micropaleontological and palaeoecological research. This study examines fossilized microorganisms and related microtextures in a recent black smoker from the Roman Ruins hydrothermal vent site, Eastern Manus Basin offshore of Papua New Guinea. Whereas the center of the examined sulfide chimney is dominated by high‐temperature mineralogy (chalcopyrite and dendritic sphalerite), filamentous and coccoidal biomorphs occur in an outer, warm zone of mixing between hydrothermal fluids and seawater, which is indicated by their occurrence within colloform and botryoidal pyrite of barite–pyrite coprecipitates. Both morphotypes can be interpreted as thermophilic microorganisms based on their occurrence in a high‐temperature habitat. Their separate (non‐commensal) occurrence hints at sensitivities to microenvironmental conditions, which is expectable for strong temperature, pH, and redox gradients at the walls of deep‐sea hydrothermal chimneys. Whereas both morphotypes experienced mild thermal overprint, taphonomic differences exist: (i) spaces left by cells in filamentous fossils are predominately filled by silica, whereas inter/extracellular features (crosswalls/septae and outer sheaths) are pyritized; (ii) coccoidal fossils show both silica‐ and pyrite‐infilled interiors, and generally better preservation of cell walls. These different manifestations presumably relate to an interplay between microenvironmental and biological factors, potentially contrasting metabolisms, and differences in cell wall chemistries of distinct bacteria and/or archaea. A further hypothesis is that the coccoidal features represent biofilm‐forming organisms, whose organic matter derivates contributed to the formation of intimately associated wavy and wrinkly carbonaceous laminations that are at least locally distinguishable from the texture of the surrounding pyrite. Hence, the presented data provide evidence that microtextures of microbiota from hydrothermal systems can have a similar significance for palaeobiological research as those from sedimentary environments.